2020
DOI: 10.9734/ijpss/2019/v31i530222
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Structural Characterization of Rhizospheric Endomycorrhiza Communities Associated with Rice Grown in the Sahelian Zone (Chad)

Abstract: In Chad, rice is grown for its starchy seeds or caryopses, but is also for consumption in the form of seeds pasta with soup. However, little or no work has been conducted in Chad to assess the composition of endomycorrhiza community inhabiting the plant rice rhizospheres. Hence, the main objective of this study was to investigate on native endomycorrhiza that are efficient to establish a symbiotic relationship with two rice varieties in the Sahelian zone in Chad. Two rice varieties were grown in a pot experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…These seeds (Figure 1) were graceously provided by the Agricultural research station in the Tandjilé region of Chad. AMF spores were isolated from soils in four regions of Chad by Nadjilom et al [22], using the two above cited rice varieties as trapping plants. Endomycorrhizal inoculants were obtained by massive multiplication of the isolated spores per rice variety and for each of the four soil sampling sites, using the modified method as described by Brundrett [23].…”
Section: Biological Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…These seeds (Figure 1) were graceously provided by the Agricultural research station in the Tandjilé region of Chad. AMF spores were isolated from soils in four regions of Chad by Nadjilom et al [22], using the two above cited rice varieties as trapping plants. Endomycorrhizal inoculants were obtained by massive multiplication of the isolated spores per rice variety and for each of the four soil sampling sites, using the modified method as described by Brundrett [23].…”
Section: Biological Materialsmentioning
confidence: 99%
“…A previous research conducted in the Tandjile region-Chad has revealed the existence of more efficient indigenous AMF affiliated to local rice varietie than to Nerica rice varieties [21]. Therefore, these indigenous strains associated with rice rhizosphere in growing areas have recently been characterized [22], but their efficacity on the improvement of rice production has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The highest mycorrhization frequency was observed in the Maroua zone in the Far North (43.66%), followed by those in the Ngaoundéré zone (26.33%) in Adamawa and Tcholiré (25 , 33%) in the North; conversely, the values recorded in the areas of Guider (1.33%) and Garoua (3%) in the North are similar and are lower (p <0.0001). Nadjilom and al. (2019) have also obtained similar results on the morphological and structural diversity of the arbuscular mycorrhiza fungi community in rice rhizosphere, grown in the sahelian zone of Chad: Mycorrhization frequency variable between 4 and 7.33%.…”
Section: Demonstration Of Endomycorrhizal Symbiosismentioning
confidence: 99%
“…These interactions can be very beneficial for plants, as is the case of the symbiotic plant-fungus endomycorrhizal association (Alabouvette andCordier, 2018, Diedhiou et al, 2022). Indeed, the fungal strains involved in this symbiosis are capable of improving the plant partner's hydro-mineral nutrition (Lambers et al, 2008), drought resistance (Leyval, 2005), yield (Ngakou et al, 2007;Ngakou et al, 2020), resistance to pathogens and pests (Elsen, 2003), and nutrition in polluted environments (Chen et al, 2007, Koffi et al, 2021. In addition, these micro-organisms stabilise soil aggregates by releasing a protein substance called glomalin (Rillig and Steinberg, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these micro-organisms stabilise soil aggregates by releasing a protein substance called glomalin (Rillig and Steinberg, 2002). Therefore, the technology of this symbiosis, which is now valued in crop production, deserves to be promoted to reduce the use of inorganic fertilisers and pesticides, in order to promote ecological and sustainable agricultural production, (Ngonkeu et al, 2013;Nadjilom et al, 2019;Koffi et al, 2019). On the other hand, leguminous crops such as cowpea, and groundnut contribute enormously to soil fertilisation through symbiotic fixation of atmospheric nitrogen (Bado, 2002).…”
Section: Introductionmentioning
confidence: 99%